Detection of multitone interference in slow frequency-hopped communication systems - Khor, Danny Jia Jie (Nanyang Technological University, 2022)
In the current digital age, digital communication systems are more preferred as digital signals are less affected by the effect of distortion, noise, and interference. Digital circuits are also more reliable, easier to design and much cheaper as compared to analog circuits. In digital communications, there are several modulation techniques but we will be focusing on frequency-hopped spread spectrum method that is widely employed for the military and commercial usages due to its high resistance towards interference and jamming.